Search for t(t)over-barH production in the all-jet final state in proton-proton collisions root s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Link, 2018)
A search is presented for the associated production of a Higgs boson with a top quark pair in the all-jet final state. Events containing seven or more jets are selected from a sample of proton-proton collisions at √ s = 13 TeV collected with the CMS detector at the LHC in 2016, corresponding to an integrated luminosity of 35.9 fb−1 . To separate the t¯tH signal from the irreducible t¯t + bb background, the analysis assigns leading order ¯ matrix element signal and background probability densities to each event. A likelihoodratio statistic based on these probability densities is used to extract the signal. The results are provided in terms of an observed t¯tH signal strength relative to the standard model production cross section µ = σ/σSM, assuming a Higgs boson mass of 125 GeV. The best fit value is ˆµ = 0.9 ± 0.7(stat) ± 1.3(syst) = 0.9 ± 1.5 (tot), and the observed and expected upper limits are, respectively, µ < 3.8 and < 3.1 at 95% confidence levels.